2001
DOI: 10.1063/1.1428109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lattice strain and defects on the superconductivity of MgB2

Abstract: The influence of lattice strain and Mg vacancies on the superconducting properties of MgB2 samples has been investigated. High quality samples with sharp superconducting transitions were synthesized. The variation in lattice strain and Mg vacancy concentrations were obtained by varying the synthesis conditions. It was found that high strain (~1%) and the presence of Mg vacancies (~ 5 %) resulted in lowering the Tc by only 2 K.Comment: 3 figures, HTML+GIF format to be published in AP

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
114
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 145 publications
(124 citation statements)
references
References 12 publications
10
114
0
Order By: Relevance
“…For the SiC doping case, an opposite trend was observed: the transition temperature increased and the lattice parameter decreased with increasing sintering temperature. 3 On the other hand, a closer correlation can be found between the transition temperature and the lattice strain estimated from a Williamson-Hall plot using the isotropic model, 11 as can be seen in Fig. 2͑d͒ or in Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…For the SiC doping case, an opposite trend was observed: the transition temperature increased and the lattice parameter decreased with increasing sintering temperature. 3 On the other hand, a closer correlation can be found between the transition temperature and the lattice strain estimated from a Williamson-Hall plot using the isotropic model, 11 as can be seen in Fig. 2͑d͒ or in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…At least under our empirical conditions, it can be argued that MgO precipitates are not the major cause of the lattice strain. Other structural defects, such as vacancies, interstitials, substitutions, or stacking faults, 11 are other possible reasons for the observed lattice strain. It has been reported that there is a correlation between the resistivity and the lattice strain, 12 as can be seen in the inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In Fig. 4 we plot the strain values vs. the RRR of our samples, 11 together with the data of Xue et al 9 . The clear dependence of RRR upon strain confirms that the residual resistance is related to lattice distortion (strain).…”
Section: Resultsmentioning
confidence: 99%
“…These can be accomplished through: (i) site-substitution into the Mg sublattice by Zr [21,22], Na [23], or similar-sized cations [24][25][26][27], (ii) site-substitution into the B sublattice by C [28][29][30][31][32] (with regard to which we note that it has been difficult to distinguish t-he influence of substitution from effect of possible C-induced lattice strain [33][34]), and (iii) increasing the connectivity between MgB 2 grains (or grain clusters) to increase the efficiency of supercurrent flow [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%